Lipotoxic Proximal Tubular Injury: A Primary Event in Diabetic Kidney Disease - Wang, Hua; Zhang, Shu; Guo, Jia (Frontiers in Medicine, 2021)
The pathogenesis of diabetic nephropathy is a complex process that has a great relationship with lipotoxicity. Since the concept of "nephrotoxicity" was proposed, many studies have confirmed that lipotoxicity plays a significant role in the progression of diabetic nephropathy and causes various renal dysfunction. This review will make a brief summary of renal injury caused by lipotoxicity that occurs primarily and predominantly in renal tubules during diabetic progression, further leading to glomerular dysfunction. The latest research suggests that lipotoxicity-mediated tubular injury may be a major event in diabetic nephropathy.